Tactical issues in managing asymmetric supply chain relationships: Insights from case studies - Shovella Santy Alrosjid; I. Nyoman Pujawan; Niniet Indah Arvitrida (Cogent Business & Management, 2022)
Imbalances in bargaining position between companies in the supply chains lead to asymmetrical relationships. While a large body of literature has addressed asymmetrical relationships in the supply chain, not much work has been exploring the issues of tactical decisions. This study presents a framework and case studies regarding how dependent manufacturers deal with tactical decisions in the context of asymmetric relationships. We conducted four case studies and looked at the tactical decisions regarding capacity flexibility, planning time fencing that reflects planning flexibility, safety stock, rescheduling frequency, and information sharing. The study suggests that (1). Most relationships in supply chains are asymmetric. A focal company with less expertise receives less power distribution but greater uncertainty in supply chain relationships. (2). When dealing with asymmetric power relationships, dependent parties create capabilities to become responsive, but most of them implement reactive tactical strategies in the form of buffering or allowing frequent changes to schedules and not effectively sharing information with trading partners.
Keywords: 650; asymmetric relationship; dependent partner; performance; supply chain; tactical strategies; uncertainty